CNC turning process parameters optimization on Aluminium 6082 alloy by using Taguchi and ANOVA. (2020) - Palaniappan, S.P.; Muthukumar, K.; Sabariraj, R.V.; Dinesh Kumar, S.; Sathish, T.
Abstract: This paper experimentally investigates the machining of Aluminium 6082 alloy to identify the optimal parameters for CNC turning process. A plan of experiments based on L27 orthogonal array was established and turning experiments were conducted with prefixed cutting parameters for Aluminium 6082 using tungsten carbide cutting tool. The turning parameters were spindle speed, feed rate and depth of cut for the responses of surface roughness and material removal rate by using Taguchi and ANOVA and also the temperature on chip compared for each experimental condition.